2020
DOI: 10.1021/acs.chemrev.9b00445
|View full text |Cite
|
Sign up to set email alerts
|

Property–Activity Relationship of Black Phosphorus at the Nano–Bio Interface: From Molecules to Organisms

Abstract: As a novel member of the two-dimensional nanomaterial family, mono- or few-layer black phosphorus (BP) with direct bandgap and high charge carrier mobility is promising in many applications such as microelectronic devices, photoelectronic devices, energy technologies, and catalysis agents. Due to its benign elemental composition (phosphorus), large surface area, electronic/photonic performances, and chemical/biological activities, BP has also demonstrated a great potential in biomedical applications including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
118
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(120 citation statements)
references
References 429 publications
1
118
0
1
Order By: Relevance
“…First, the development of cheap, easy and high yield synthetic strategies is needed for the production of large quantities of few-layer phosphorene sheets, with controlled size and morphology. To date, two of the most promising methods to realize large-scale exfoliation of BP are the electrochemical exfoliation and the shear exfoliation methods, due to their efficiency and scalability [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the development of cheap, easy and high yield synthetic strategies is needed for the production of large quantities of few-layer phosphorene sheets, with controlled size and morphology. To date, two of the most promising methods to realize large-scale exfoliation of BP are the electrochemical exfoliation and the shear exfoliation methods, due to their efficiency and scalability [56].…”
Section: Discussionmentioning
confidence: 99%
“…As far as biomedical applications are concerned, 2D nanomaterials are promising in optical imaging, biosensing, phototherapy, targeted delivery, and other fields [51][52][53][54][55][56][57]. The tunable band gap of phosphorene, which is size-dependent, allows its interaction with the electromagnetic field to be manipulated in a layer-dependent manner, in the ultraviolet (UV) and near-infrared (NIR) regions.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Although most of the studies have focused on the basic electronic characterization of the devices, BP-based FETs have been successfully applied for sensing [16][17][18] or photodetection. [19][20][21] Thanks to the very low cytotoxicity of black phosphorus in comparison to other 2D materials as graphene and transition metals dichalcogenides [22], and to its photonic properties, the application of BP in the biomedical field has grown exponentially, as recently reviewed by Qu G. and co-workers [23]. The seminal work conducted by Xie Y. et al [24] demonstrated that BP nanosheets are stable in water for a certain time and they can generate efficiently singlet oxygen under the entire visible light region, thus opening the application of BP not only in photocatalysis, but also in photothermal and photodynamic therapy (PDT).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, BP also represents a good candidate for regenerative medicine [25]. Furthermore, BP has also demonstrated great potential in biosensing, controlled drug release, and antibacterial use [23]. The sp 3 hybridization of phosphorus atoms in BP is also responsible for the presence of a lone pair on each atom.…”
Section: Introductionmentioning
confidence: 99%
“…To date, bystander effect studies have focused on post-irradiation effects [1,2], but there is growing evidence that other environmental stressors also induce damage in bystander populations, including heat stresses, photodynamic therapy, genotoxic chemicals, heavy metals, and other multiple stressors [3,4,5,6,7]. The use of nanoparticles in biology continues to increase and release to the environment are inevitable [8,9,10]. Given the inherent interactions between targeted cells and neighboring cells, it is important to understand the nontargeted effects of nanoparticles [9,11,12,13].…”
Section: Introductionmentioning
confidence: 99%